2015
DOI: 10.1002/smll.201500985
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐Triggered Controlled Drug Release from Electrospun Fibers Using Inorganic Caps for Inhibiting Cancer Relapse

Abstract: A smart, tumor-trigged, controlled drug release using inorganic "caps" with CO3 (2-) functional groups in electrospun fibers is presented for inhibiting cancer relapse. When the drug-loaded intelligent electrospun fibers encounter pathological acidic environments, the inorganic gates react with the acids and produce CO2 gas, which enables water penetration into the core of the fibers to induce rapid drug release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 34 publications
0
67
0
Order By: Relevance
“…The surfactant-free GNSs were initially synthesized according to the seed-mediated template-assisted protocol with some modifications 30. The acquired GNSs were subsequently covered by a layer of CaCO 3 , into which ICG were simultaneously entrapped 25. Transmission electron microscopy (TEM) images showed that the GNSs exhibited outstanding size uniformity with a diameter of 96 ± 7.5 nm, and dozens of branches extended from their surfaces (Figure 1A, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The surfactant-free GNSs were initially synthesized according to the seed-mediated template-assisted protocol with some modifications 30. The acquired GNSs were subsequently covered by a layer of CaCO 3 , into which ICG were simultaneously entrapped 25. Transmission electron microscopy (TEM) images showed that the GNSs exhibited outstanding size uniformity with a diameter of 96 ± 7.5 nm, and dozens of branches extended from their surfaces (Figure 1A, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction solution was kept under moderate stirring for 2 hours and GNS were acquired then. Next, calcium carbonate coating on GNSs was carried out according to Zhao's method with some modifications 25. Briefly, 1 mL of CaCl 2 (10 mg/mL) and 20 μL of ICG (500 μg/mL) were added to 50 mL as-prepared GNSs followed by moderate stirring for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations